Mobile-phone-based solution for disease outbreak reporting and surveillance - Mutegi, Lorna Mwende (Strathmore University, 2014)
Effective disease surveillance demands timely dissemination of information to parties responsible for disease prevention and control to warrant necessary action. The level of efficiency and effectiveness is dependent on the tools used for disease surveillance. The use of traditional reporting tools, such as paper based disease case reporting tools is a compromise to timeliness, completeness, and correctness of reported data. Mobile applications are a revolution in efficiency to all sectors. With the current Kenyan mobile penetration nearing 78%, there are an unprecedented opportunities that Kenya can tap to improve the state of disease surveillance. This study analyzes the current state of disease surveillance models in Kenya to identify its challenges. A comprehensive investigation on previous research done in Kenya and internationally is covered. International research focuses on the two world’s largest economies; China and United States of America. The key data collection instrument employed was questionnaire. The collected data was analyzed using both qualitative and quantitative methods of data analysis. The results of the data analysis helped inform System Analysis and Design stage and Applications development (Mobile and Web Applications). A USSD based mobile application was developed. This tool offers an interactive menu based platform where users can report disease outbreaks. A web application was also designed. This application provides information on the state of disease surveillance to disease surveillance focal persons and the public. The application also provides a portal via which epidemiologists or medical lab technicians can view reported disease outbreaks and record results of the epidemiological tests carried out to confirm the outbreak. They can also recommend prevention and control measures to take for each case. System testing was done to ensure correctness, completeness, reliability, and usability of both applications.
Submitted in partial fulfilment of the requirements for the Degree of Master of Science in Mobile Telecommunication and Innovation
Keywords: Mobile solution; Disease Outbreak Reporting; Surveillance